Qualitative comparative analysis of the personal traits of managers, scientists, and innovators in corporate science - Jubalt Rafael Alvarez-Salazar; Pedro Martín Bernal-Pérez (Journal of Innovation & Knowledge (JIK), 2025)
This study examined the personal traits that contribute to the success of corporate science projects in Peru by focusing on the roles of CEOs, scientists, and innovators. Although Peru has seen economic progress in recent decades, integrating scientific research into business strategies requires improvement, reflecting a common trend in emerging economies. Through a fuzzy set qualitative comparative analysis (fsQCA) and a sample of 56 participants, the configurations of personal characteristics that contribute to the success of such projects were identified. The results indicate that success depends not on a single attribute but on a combination of various capabilities. This study emphasizes the importance of adaptability and collaboration among key actors and suggests a management approach that blends technical skills with interpersonal competencies. The practical implications of this study emphasize the need to align corporate leadership with scientific and market dynamics, foster empathy and teamwork, and leverage external networks to enhance innovation. Strategies must be adapted to the specificities of emerging economies where science, technology, and innovation systems are still developing.
Keywords: L21; M12; O31; O32; 650; Corporate science; Transformational leadership; Open innovation; Knowledge appropriation; fsQCA; Emerging economy